2013
DOI: 10.1590/s1516-14392013005000192
|View full text |Cite
|
Sign up to set email alerts
|

Effects of precursor concentration and reaction time on sonochemically synthesized ZnO nanoparticles

Abstract: The sonochemical reaction between Zn(NO 3 ) 2 and hexamethylenetetramine (HMT) resulted in different products depending on amounts of Zn(II) cations in the aqueous solution. Crystalline phase pure ZnO nanoparticles were obtained by using 0.05 M Zn(NO 3 ) 2 -HMT. This single phase was formed by low power sonication for 20 min in an ultrasonic bath at ambient conditions and its morphology did not change for the next 60 min. Higher concentrations of precursors (0.1 and 0.5 M) led to a mixture of zinc compounds in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 26 publications
5
44
1
Order By: Relevance
“…Intensive studies have been done on various factors, such as precursor concentrations [8,9], temperature [10,11], duration [12], surfactant concentration [7], dopant concentration [6], solvent medium [13], pH of reaction mixture [14] and source of light during synthesis [15], which individually and collectively affect the shape, size and optical properties of ZnO. Various researchers [16][17][18] suggested that NaOH concentration plays a vital role in determining the morphology, size and optical bandgap of obtained nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive studies have been done on various factors, such as precursor concentrations [8,9], temperature [10,11], duration [12], surfactant concentration [7], dopant concentration [6], solvent medium [13], pH of reaction mixture [14] and source of light during synthesis [15], which individually and collectively affect the shape, size and optical properties of ZnO. Various researchers [16][17][18] suggested that NaOH concentration plays a vital role in determining the morphology, size and optical bandgap of obtained nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above analysis and previously demonstrated strong correlation between the surface defects and optoelectronic properties of ZnO materials [28,[48][49][50], one can expect that the SPV decays would be remarkably different in the SC samples obtained at different stirring times. This is exactly what is seen in Fig.…”
Section: Spv and Pl Decaysmentioning
confidence: 73%
“…This is evident that, despite the simplicity and moderate conditions employed in this study, smaller crystallite sizes could be produced. According to [39], a crystallite size of 21.59 nm and 36.89 nm can be obtained for ZnO from KOH and NaOH, respectively in a sol-gel method. Their reaction time and drying temperature were maintained at 2 hours and 70 o C. In another study by [24], an average crystallite size of 33 nm was recorded in a solvothermal method using Zinc acetate and Triethanolamine (TEA) media.…”
Section: Xrd Resultsmentioning
confidence: 99%